Neural Function Recovery and Safety of Mild Hypothermia Therapy Combined with Monosialotetrahexosylganglioside on Neonatal Asphyxia Complicated by Hypoxic Ischemic Encephalopathy. (27th December 2021) - Ge, Jingjing; Jiao, Xiaoling; Qi, Fanlin; Li, Hui
Abstract : Objective . To explore the effect and safety of mild hypothermia therapy combined with monosialotetrahexosylganglioside (GM1) on neural function recovery of neonatal asphyxia complicated by hypoxic ischemic encephalopathy (HIE). Methods . The clinical data of 90 neonates with HIE were retrospectively analyzed. According to the treatment methods, the neonates were divided into a routine group, a mild hypothermia group, and a combination group, with 30 cases in each group. The differences in neural function recovery, biochemical indexes, clinical signs recovery, efficacy, and complications were observed in the three groups after treatment. Results . After treatment, the score of neonatal behavioral neurological assessment (NBNA) and level of superoxide dismutase (SOD) in the combination group were higher than those of the other two groups (P < 0.05 ). The levels of neuron-specific enolase (NSE), S-100 β protein, and plasma neuropeptide Y (NPY) in the combination group were lower than those in the other two groups, and the recovery time of consciousness, muscle tension, and reflex was shorter (P < 0.05 ). The combination group showed higher total effective rate and lower incidence of complications as compared with the other two groups (P < 0.05 ). Conclusion . Mild hypothermia therapy combined with GM1 for the treatment of neonatal asphyxia complicated by HIE can promote the recovery of neural function and reduce the incidence of complications in neonates.